Approximate Analytic Solution for Harmonic Oscillator with Fractional Order Damping Term (International Journal of Food and Nutritional Sciences, 2022)
In this paper, analytical and numerical results are reported on the approximate solution for harmonicoscillator equation with fractional order damping term by Adomian Decomposition Method (ADM). The ADM solutionis then compared with the well known series solution of the problem. It is found that the results lead to an excellentagreement. The graphical representation of the solution has been presented for different values of damping coefficientand frequency of the oscillator.